Speaking for Our Lives : Historic Speeches and Rhetoric for Gay and Lesbian Rights (1892-2000). - Ridinger, Robert B. (Taylor and Francis, 2014)
Read the words they risked everything for! This landmark volume collects more than a hundred years of the most important public rhetoric on gay and lesbian subjects. In the days when homosexuality was mentioned only in whispers, a few brave souls stood up to speak for the rights of sexual minorities. In Speaking for Our Lives: Historic Speeches and Rhetoric for Gay and Lesbian Rights (1892-2000), their stirring words have finally been gathered together, along with the political manifestoes, broadsheets, and performance pieces of the gay and lesbian liberation movement.